Analisis Pengaruh Capital Intensity, Leverage, Profitabilitas, Ukuran Perusahaan, dan Perputaran Persediaan terhadap Agresivitas Pajak - Qorin Nurul Iffah; Amrizal Amrizal (Jurnal Manajemen, 2022)
The goal of this research is to look at the elements that influence tax aggression in one way or another. Capital intensity, leverage, profitability, company size, and inventory turnover are the independent variables in this study. Tax aggressiveness, which is determined by ETR, is the dependent variable in this study. The study's population consisted of 19 mining businesses in the oil and gas sub-sector that were listed on the Indonesia Stock Exchange (IDX) between 2016 and 2020. The sample for this study was determined using the purposive sampling approach, which yielded a sample of 7 organizations depending on specified criteria. Multiple linear regression was used to examine the data with the SPSS version 22 tool. As a result, it is known that capital intensity, leverage, profitability, and company size have no effect on tax aggression. Meanwhile, simultaneously capital intensity, leverage, profitability, firm size, and inventory turnover all have a positive impact on tax aggressiveness, as evidenced by the Adjusted R Square value of 0.241, indicating that the independent variable has a 24.1 percent influence on the dependent variable, with the remaining 75.9% influenced by variables not included in this study.